Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(2x^2-8x\Leftrightarrow2x\left(x-4\right)\)
b) \(2x^2-4x+2\Leftrightarrow2\left(x^2-2x+1\right)=2\left(x-1\right)^2\)
c) \(3x^3+12x^2+12x\Leftrightarrow3x\left(x^2+4x+4\right)=3x\left(x+2\right)^2\)
a, <=> (x-1).(x-6) = 0
<=> x=1 hoặc x=6
b, <=> (x+1).(2x-5) = 0
<=> x=-1 hoặc x=5/2
c, <=> (2x-5).(2x-1) = 0
<=> x=5/2 hoặc x=1/2
d, <=> (x^2-x+1).(x^2+1) = 0
=> pt vô nghiệm vì x^2-x+1 và x^2+1 đều > 0
Tk mk nha
a) x2 - 7x + 6 = 0
<=> x2 - 6x - x + 6 = 0
<=>( x - 6 ) ( x - 1 ) = 0
<=> x - 6 = 0 hoặc x - 1 = 0
1. x - 6 = 0
<=> x = 6
2. x - 1 = 0
<=> x = 1
Vậy ......
b) 2x2 - 3x - 5 = 0
<=> 2x2 + 2x - 5x - 5 = 0
<=> ( x + 1 ) ( 2x - 5 ) = 0
<=> x + 1 = 0 hoặc 2x - 5 = 0
1. x + 1 = 0
<=> x = -1
2. 2x - 5 = 0
<=> x = 2.5
Vậy ............
c) 4x2 - 12x + 5 = 0
<=> 4x2 - 2x - 10x + 5 = 0
<=> 2x ( 2x - 1 ) - 5( 2x - 1 ) = 0
<=> ( 2x - 1 ) ( 2x - 5 ) = 0
<=> 2x - 1 = 0 hoặc 2x - 5 = 0
1. 2x - 1 = 0
<=> x = 0.5
2. 2x - 5 = 0
<=> x = 2.5
Vậy ....................
d) x4 - x3 + 2x2 - x + 1 = 0
a/ 4x2+x-4x-1
x(4x+1)-(4x+1)
(4x+1)(x-1)
b/(6-11)x2+3
-5x2+3
c/x2-3xy-4xy+12y2
x(x-3y)-4y(x-3y)
(x-3y)(x-4y)
d/(x-y)2+3(x-y)
(x-y+3)(x-y)
e/(2-12)x2+17x-2
-10x2+17x-2
g/x3+x2+2x2+2x+4x+4
x2(x+1)+2x(x+1)+4(x+1)
(x+1)(x2+2x+4)
h/x3+2x2+7x2+14x+12x+24
x2(x+2)+7x(x+2)+12(x+2)
(x+2)(x2+7x+12)
(x+2)(x2+4x+3x+12)
(x+2)(x+4)(x+3)
Giải:
a) 4x2 - 3x - 1 = 4x2 - 4x + x - 1 = 4x(x - 1) + (x -1) = (x - 1)(4x +1)
b) 6x2 - 11x + 3 = 6x2 - 2x - 9x + 3 = 2x(3x - 1) - 3(3x - 1) = (3x - 1)(2x - 3)
c) x2 - 7xy + 12y2 = x2 - 6xy + 9y2 - xy +3y2 = (x - 3y)2 - y(x - 3y) = (x - 3y)( x - 3y - y) = (x - 3y)(x - 4y)
d) x2 - 2xy + y2 + 3x - 3y = (x - y)2 + 3(x - y) = (x - y)(x - y + 3)
e)Sửa đề: x2 → x3
2x3 - 12x2 + 17x - 2 = 2x3 - 4x2 - 8x2 + 16x + x - 2 = (2x2- 8x + 1)(x -2)
f) x3 - 3x + 2 = x3 - x - 2x + 2 = x(x + 1)(x - 1) - 2(x - 1) = (x - 1)(x2 + x - 2) = (x - 1)2(x + 2)
g) x3 + 3x2 + 6x + 4 = x3 + 3x2 + 3x + 1 + 3x + 3 = (x +1)3 + (x + 1) = (x + 1)(x2 + 2x + 4 )
h) x3 + 9x2 + 26x + 24 = x3 + 4x2 + 5x2 + 20x + 6x + 24 = (x + 4)(x2 + 5x + 6) = (x + 4)(x + 3)(x + 2)ư
Chúc bạn học tốt@@
Câu 1:
\(3x\left(12x+4\right)+9x\left(4x+3\right)\)
\(\Leftrightarrow3x\left(12x+4\right)+3x\left[3.\left(4x+3\right)\right]\)
\(\Leftrightarrow3x\left(12x+4\right)+3x\left(12x+6\right)\)
\(\Leftrightarrow3x\left[12x+4+12x+6\right]\)
\(\Leftrightarrow3x.\left(24x+10\right)\)
\(\Leftrightarrow72x^2+30x\)
Câu 2:
\(x\left(5+2x\right)+2x^2\left(x-1\right)\)
\(\Leftrightarrow5x+2x^2+2x^3-2x^2\)
\(\Leftrightarrow2x^3+5x\)
Đề 1
- Use different phrasing or notations
- Enter whole words instead of abbreviations
- Avoid mixing mathemaal and other notations
- Check your spelling
- Give your input in English
- Wolfram|Alpha answers specific questions rather than explaining general topicsEnter "2 cups of sugar", not "nutrition information"
- You can only get answers about objective factsTry "highest mountain", not "most beautiful painting"
- Only what is known is known to Wolfram|AlphaAsk "how many men in Mauritania", not "how many monsters in Loch Ness"
- Only public information is availableRequest "GDP of France", not "home phone of Michael Jordan"
Input:
Open code
Inequality plot:
Open code
Alternate forms:
Open code
Open code
Expanded form:
Open code
Solution:
- Approximate form
Open code
Integer solution:
Open code
\(4x^2-28=0\)
\(\Leftrightarrow4\left(x^2-7\right)=0\)
\(\Leftrightarrow x^2-7=0\)
\(\Leftrightarrow x^2=7\)
\(\Leftrightarrow x=\pm\sqrt{7}\)
a. (x + 3).(x2 - 1)
= x.x2 - x.1 + 3.x2 - 3.1
= x3 - x + 3x2 - 3
= x3 + 3x2 - x - 3
b. (3x + 2).(4x - 1)
= 3x.4x - 3x + 2.4x - 2
= 12x2 - 3x + 8x - 2
= 12x2 + 5x - 2
c. (2x - 3).(3x + 2)
= 2x.3x + 2x.2 - 3.3x - 3.2
= 6x2 + 4x - 9x - 6
= 6x2 - 5x - 6
d. (12x - 5).(4x + 1)
= 12x.4x + 12x - 5.4x - 5
= 48x2 + 12x - 20x - 5
= 48x2 - 8x - 5
e. (x - 3).(x2 + 3x + 9)
= x.x2 + x.3x + x.9 - 3x2 - 3.3x - 3.9
= x3 + 3x2 + 9x - 3x2 - 9x - 27
= x3 - 27 (Đây là dạng HĐT x3 - 33)